1993
DOI: 10.1002/ajmg.1320470812
|View full text |Cite
|
Sign up to set email alerts
|

Malformations and deformations in abdominal pregnancy

Abstract: Abdominal gestation is a relatively uncommon complication of pregnancy. Previous reports describe a high incidence of fetal deformations and mortality as well as maternal mortality. A case of twin abdominal gestation is presented and the literature concerning abdominal pregnancy since 1809 is reviewed. The survival rate of liveborn infants of 30 or more weeks gestation was 63%. The maternal mortality rate since 1809 was 18.2%, but this has decreased to 4.5% during the last 20 years. The combined rate of malfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 118 publications
0
45
0
5
Order By: Relevance
“…Pulmonary hypoplasia, pressure deformities, and foetal growth restriction due to placental insufficiency are the most eminent causes leading to neonatal complications. Typical deformities include limb defects, facial and cranial asymmetry, joint abnormalities and central nervous malformation (28). These pregnancies usually do not extend to 37 weeks and usually end up with foetal loss (29).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary hypoplasia, pressure deformities, and foetal growth restriction due to placental insufficiency are the most eminent causes leading to neonatal complications. Typical deformities include limb defects, facial and cranial asymmetry, joint abnormalities and central nervous malformation (28). These pregnancies usually do not extend to 37 weeks and usually end up with foetal loss (29).…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of foetal malformations as high as 40% associated with abdominal pregnancies and only 50% of these babies survive up to one week post delivery. 8,9 In his extensive review, Stevens found some varying degrees of deformations and malformations in 21.4% of these infants 10 . In this case that has been presented; no malformation has been found on the child.…”
Section: Discussionmentioning
confidence: 98%
“…The most frequent and reliable finding includes an empty uterus seen separate from the fetus. 14,15 Other signs include an ectopic intra-abdominal placenta, pseudo placenta praevia appearance, oligohydramnios, lack of myometrial tissue around fetus, fetus and placenta obscured by overlying bowel gas and abnormal fetal presentation.…”
Section: Discussionmentioning
confidence: 99%